Implementation of Pancasila Values among Students in Implementing Government Policies in the Education Sector during the COVID-19 Pandemic - Amelia Amanda; Uwe Barroso; Matteson Niva (International Journal of Educational Narratives, 2023)
Background. The outbreak of the Covid-19 outbreak in Indonesia has prompted the government to issue many new policies related to various fields of community life. One of them is a policy in the field of education, namely through the establishment of the LFH (Learning from Home) policy for all levels of education. The problem that arises is the demand for changes in student behavior from traditional learning methods to independent learning patterns. Purpose. The purpose of this study is to determine how students apply Pancasila values in implementing learning in the Covid-19 Pandemic era in line with government policies. Method. The research was conducted with a quantitative approach, which began with a literature study to find out aspects related to Pancasila values, LFH learning methods and health policies in the Covid-19 Pandemic era. Based on the results of the literature study, a questionnaire was developed to collect data from students. The questionnaire was made an online version using google form so that it was easily filled in by respondents, namely 30 new Tadris English students. Results. The research findings are interesting to note, namely the majority of respondents (85%) argue that government policies in the field of education in the current Covid-19 Pandemic era have not been carried out effectively. In fact (67.5%) students stated that there was a decrease in learning motivation among students. This finding needs to be immediately anticipated by decision-makers in higher education. Conclusion. The values of Pancasila that are applied at this time are Fair and Civilized Humanity and Indonesian Unity.